Efektifitas Metode Penyampaian Pendidikan Seksual dari Persepsi Viewer pada Platform YouTube - Pratama, Armanda Prastiyan (Universitas Al-Qolam Malang, 2025)
Sex education is not yet a specific subject in education in Indonesia at this time. However, many schools in Indonesia have implicitly incorporated elements of sex education into some subjects, such as: Biology, Religious Education, and Guidance and Counseling. The problem that arises is how to deliver sex education effectively as a preventative measure against sexual deviation, both as perpetrators and as victims. The reorientation of sex education seeks to reformulate the purpose of sex education for adolescents. This research aims to determine the delivery method and its effectiveness viewed from the perception of viewers on the YouTube platform. This study uses a qualitative approach with an explorative method. The delivery of sexual education through YouTube can be very appealing to children and adolescents, because the content created can be lighter and adapted to the characteristics of the content consumer. This can be identified from the comment section which contains responses from the viewers towards the uploaded content. The majority of viewers agree that sexual education content is very important to be delivered to children and adolescents, in order to prevent sexual violence which may occur anywhere.